2020
DOI: 10.3126/nje.v10i2.27941
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and readiness of health care workers in implementing Pradhan Mantri Jan Arogya Yojana in a tertiary care hospital at Rishikesh

Abstract: Background: Right to health is one among the important components of basic human rights. The Government of India had announced “Ayushman Bharat for a new India-2022”, during 2018-19 parliament budget sessions with two components namely, Health and wellness centers for strengthening primary care and national health protection scheme now known as Pradhan Mantri Jan Arogya Yojana (PMJAY) for enabling access to secondary and tertiary health care by giving health (6). Current study was conducted to assess a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Faculty had a much higher awareness score than senior residents, in contrast to our study, which found no significant difference, even though faculty had a slightly higher mean awareness score than resident doctors. Similar to our study, they found that the relationship between awareness and readiness was correlated with Pearson's correlation of 0.206 and was statistically significant [ 11 ].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Faculty had a much higher awareness score than senior residents, in contrast to our study, which found no significant difference, even though faculty had a slightly higher mean awareness score than resident doctors. Similar to our study, they found that the relationship between awareness and readiness was correlated with Pearson's correlation of 0.206 and was statistically significant [ 11 ].…”
Section: Discussionsupporting
confidence: 87%
“…This indicates how much better awareness can be achieved by doing training and awareness workshops before the program's launch. The mean awareness and readiness scores among medical and surgical branches were not statistically significant, according to a study conducted by Reddy NK et al [ 11 ]. Faculty had a much higher awareness score than senior residents, in contrast to our study, which found no significant difference, even though faculty had a slightly higher mean awareness score than resident doctors.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations